Pengaruh Digitalisasi Terhadap Gaya Hidup, Kesehatan Mental Dan Interaksi Sosial Gen Z Dan Alpha: Perspektif Generasi Swipe Di Era Digital - Aldi Friyatna Dira; Kurniawan Prambudi Utomo Kurniawan; Devy Sofyanty (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
This study aims to analyze the impact of digitalization on lifestyle, mental health, and social interaction among Generation Z and Generation Alpha in Bekasi City. Utilizing a quantitative approach with a survey method, data were collected from students and university students using a structured Likert scale questionnaire. The analysis was conducted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) to examine the relationships between latent variables. The results indicate that digitalization significantly influences lifestyle, mental well-being, and social interaction. It shapes daily habits that are increasingly connected to digital technology, influencing consumption patterns and activity management among the youth. However, excessive use of digital media also contributes to psychological strain and a decline in the quality of face-to-face social relationships. These findings suggest that Generation Z and Alpha live in a highly digitalized environment, necessitating guidance, digital literacy education, and supportive social policies to maintain a balance between technology usage and the psychological and social well-being of young people